(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The idea of Self Help Group has its underlying foundations in rural areas and it has been mooted along the rural and semi urban women to improve their living conditions. Despite the fact that it is relevant to men in our country, yet it has been increasingly fruitful just among women and they can begin economic exercises through SHG development. In India, this scheme is executed with the help of NABARD as a principle nodal office in rural development. It is self-employment generation scheme for particularly rural women, who don’t have their very own advantages. The word ’empowerment’ signifies giving force. Empowerment gives a more noteworthy access to knowledge and resources, more independence in basic leadership, more prominent capacity to plan lives, more power over the conditions which impact lives, and opportunity from traditions, convictions and practices. Along these lines, empowerment of women an objective in itself, however key to all global development objectives. Empowerment is a functioning multidimensional process to empower women to understand their character and power in all circles of life. This paper looks at the women empowerment through SHGs and furthermore clarifies the present position of women empowerment in India.This examination manages the comprehension of job of Self Help Group (SHG) in Socio-economic development of rural women of the province of Goa. The empowerment of women is imperative for the development and growth of the country. Emphatically inspiring women and carrying them into the standard of development is a noteworthy worry for the Government of India. That was the reason year 2001 was proclaimed as the Time of women Empowerment Women’s empowerment is basic to the socio economic advancement of the network and to carry women into the standard of national development has, thusly, been a noteworthy worry of the government.